Resource-saving technologies of derivatization of functional nanostructured coatings by high-speed application methods - Igor N. Kravchenko; Maria Yu. Karelina; Elena M. Zubrilina; Anastasiya A. Kolomeychenko (Advanced Engineering Research)
The work objective is to study new application methods based on the resource-saving technologies for nanostructured coatings with different functionality. The main task of the work is investigating modern efficient methods to increase strength, corrosion resistance, and wearability. The subject of study is high-speed application methods for anti-corrosion and wear-resistant coatings that significantly improve the durability and reliability of products. Design, technological features, specifications, and a scope of applicability of various installation models for high-speed deposition methods, including a gas-plasma technique, are described. The analysis results of the basic physical, mechanical and performance properties of the coatings obtained with the compact high-performance process equipment are presented. As a result of this work, it is shown that coatings obtained by the high-speed methods, unlike the subsonic methods, are characterized by the high performance. The paper also presents perspectives for development of the processing methods of the multifunctional coating application, the improvement of equipment and materials. The data obtained can be used for designing processes of applying dense coatings of consistent quality on the complex products made from nearly all metals and alloys. The results obtained are applicable in the mechanical engineering, repair production, aviation, energy engineering, etc.